A Multiple Resonant Frequencies Circular Reconfigurable Antenna Investigated with Wireless Powering in a Concrete Block - Shishir Shanker Punjala; Niki Pissinou; Kia Makki (International Journal of Antennas and Propagation)
A novel broadband reconfigurable antenna design that can cover different frequency bands is presented. This antenna has multiple resonant frequencies. The reflection coefficient graphs for this antenna are presented in this paper. The new proposed design was investigated along with RF MEMS switches and the results are also presented. Investigations were carried out to check the efficiency of the antenna in the wireless powering domain. The antenna was placed in a concrete block and its result comparison to that of a dipole antenna is also presented in this paper.